Improving Statistical Analysis in Supporting Big Data Era for SMA Negeri 1 Krembung Teachers - Rahmi, Nur Silviyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Classroom Action Research (CAR) is a research type conducted within the classroom environment to enhance the learning process. To collaborates in organizing community service through training to empower the educational community at SMA Negeri 1 Krembung. To assess the community service program's effectiveness, pre-test and post-test analyses were carried out using the t-test. By applying the Wilcoxon Signed Rank Test hypothesis, a significant difference was identified in statistical and data science-based analysis skills before and after the community service program implementation. The ability to analyze based on statistics and data science has improved, evident from the post-test mean rank value surpassing the pre-test mean rank value (11.08 > 6.33). Consequently, it can be concluded that repeating training activities is essential to enhance statistical and data science-based analysis skills in the big data era and to provide a deeper understanding of Classroom Action Research.